Implementasi Perencanaan Pendidikan dalam Meningkatkan Karakter Bangsa Melalui Penguatan Pelaksanaan Kurikulum di SMPN 2 Payung Sekaki - Event, Diana; Heviana, Elsi; Rahayu, Ivo Gana; Aiga, Ruspel; Asmendri, Asmendri; Sari, Milya (Peneliti.net, 2024)
The large number of deviations and juvenile behavior among students is a worrying phenomenon, so the education sector is currently working hard to provide character education for students. Therefore, this research aims to provide a description regarding the implementation of educational planning in improving national character by strengthening curriculum implementation. The research carried out was qualitative in the form of a case study. Primary data was obtained from observations and interviews with school principals, teachers and students, while secondary data was obtained through literature studies from supporting books and scientific journals that were relevant to the research topic. The findings show that the implementation of educational planning carried out at SMPN 2 Payung Sekaki is through strengthening the curriculum to improve national character, namely by integrating character education values in the syllabus and lesson plans, holding routine and spontaneous activities to shape students' personal character, and holding extracurricular activities. As for developing the character of this nation, schools also have a curriculum based on character education which is realized from various school cultures which have been passed down from generation to generation as habituation, for example the 3S culture, religious ritual activities such as praying and worshiping together, as well as democratic decision making. The various forms of educational planning are known to be a means for SMPN 2 Payung to form students who have character and can improve the character of the nation.